Shock-induced spall in single and nanocrystalline SiC. (November 2017) - Li, W.H.; Yao, X.H.; Branicio, P.S.; Zhang, X.Q.; Zhang, N.B.
Abstract: Shock-induced spall in SiC is investigated via high strain-rate loading molecular dynamics simulations. The dynamic response under different shock intensities is characterized along the low-index 3C-SiC crystallographic directions, [001], [110], and [111], and in a nanocrystalline sample with 5 nm average grain size. The simulation results show that all single crystal samples generate elastic, plastic, and structural phase transformation waves for increasing particle velocities in good agreement with previous investigations. However, crystal anisotropy effects affect the exact shock response and the corresponding wave structures. The Hugoniot elastic limit is significantly higher along the [111] and [110] directions while the patterns of plastic deformation, based on deformation twinning, contrast along the three crystallographic directions. The spall behavior, both for single and nanocrystalline samples vary from classical to micro-spall. The predicted spall strength is at maximum along the [111] direction, at 34 GPa, followed by the [110], and [001] directions, at 32 and 30 GPa, respectively. Nanocrystalline SiC displays a spall strength over 66.7% lower than single crystals. Spall strengths from direct and indirect methods agree well for both classical and micro-spall regimes after applying an elastic-plastic correction and considering the change in sound velocity, in particular for the case where the structural phase transformation occurs. Graphical abstract: Image